Environmental Protection in Context of Tourist Use - Rusev, Rusi (Research Papers, 2018)
The issue of environmental protection has become more and more relevant. The main objective is to present the different environmental protection activities in the context of tourist use. Main tasks are to be explored the strengths and weaknesses, opportunities and threats of Bulgaria as a tourist destination, analyzed are public sources of information for identifying alternative forms of sustainable tourism. The interest of tourists and the local population and authorities is of the utmost importance to reduce the negative impact on nature.
Keywords: Exploitation; Pollution; Environment; Tourism